Pemanfaatan media pembelajaran digital padlet sebagai solusi pembelajaran di masa pandemi Covid-19 - Budi Santoso, Richo (Educenter : Jurnal Ilmiah Pendidikan, 2022)
This research aims to get an idea of how far the use of Padlet learning media as a learning solution in the covid-19 pandemic. The research methods used in this re-search are qualitative descriptive. Data collection techniques in the form of literature studies are used to describe padlet applications. Then continued with descriptive analysis to provide an overview of the use of Padlet learning media as a learning solu-tion in the covid-19 pandemic. Padlet is a digital learning medium available in the form of web and applications. Utilization of Padlet learning media during the covid-19 pandemic is as follows: a liaison between educators and learners to be able to interact on distance learning without virtual face-to-face; Comment features that educators can use to open discussion topics without worrying about the topic will be drowned out by the response of learners; Padlets can be used by educators as a place to store files of tasks from learners; Padlets can be used to motivate and see the re-sponse of learners.